B04 Alternative Splicing In Htt. (17th September 2014) - Hughes, A; Mort, M; Carlisle, F; Jones, L
Abstract : Background: HD pathogenic mechanisms are complex with studies largely centred on the mutant HTT protein. The role of the mutant HTT transcript in HD pathogenesis has also been considered more recently, with growing evidence for RNA toxicity mechanisms and an increasing awareness that HTT is alternatively spliced. Our previous work demonstrated the presence of novel HTT splice variants in mouse with differential expression shown between HdhQ150/Q150 and wild type cerebellum. Aims: The aim of this study was to determine whether any alternative transcripts of HTT are present in human brain and whether their expression levels show association with HD. Methods/techniques: RNA was extracted from HD patient and control brain and reverse transcribed prior to PCR of overlapping amplicons spanning the whole length of HTT. Bands on gel electrophoresis, in addition to those expected to arise from the full length transcript, were isolated and sequenced to confirm identity. Bioinformatic techniques were used to model the variants most likely to impact the HTT protein. Results/outcome: 23 novel HTT splice variants were detected in human brain. Protein homology modelling used to assess the functional significance of certain in-frame variants demonstrated a novel HTT isoform lacking a known HEAT repeat resulting in the loss of a predicted protein binding site in HTT. Conclusions: Several novel human HTT RNA species have been discovered here which provide a focus in the analysis of RNA sequencing datasets. They also have implications for HD therapeutic avenues such as RNA therapies and the correction of mis-splicing in disease. Further work is required to demonstrate whether these variants encode novel HTT protein isoforms and whether they play a role in the pathogenesis of HD.